(untitled) (Research, Society and Development, 2022)
Purpose: To analyze the influence of the breastfeeding profile on the occlusal characteristics of the primary dentition in children participating and not participating in an educational-preventive dental program as well as its influence in these aspects. Methods: This cross-sectional study was carried out using a questionnaire filled in by the guardians combined with the examination of the occlusal characteristics of 400 children aged between 27 and 48 months, divided into 2 groups, 200 participants of a preventive dental program, Baby Clinic (BC), and 200 from schools from the city, not participating in a preventive dental program. The questionnaire included retrospective information on duration, type and form of breastfeeding and non-nutritive sucking habits (NNSH). Clinical evaluation of dental occlusion was also performed, using the malocclusion index recommended by the World Health Organization. Data were analyzed using the chi-square test. Results: In both groups, a high percentage of mothers breastfed their children (90% BC; 84.5% schools); high percentage of children had NNSH (64.5% BC; 57.5% schools), as well as a high rate of dental malocclusion (63% BC; 58% schools), the main one being anterior open bite (20.5% BC; 15% schools). In both groups, a lower occurrence of malocclusion was observed in children who were exclusively breastfed for up to six months (29.5% BC; 16.5% schools). Conclusions: our results indicated that children who were breastfed up to 6 months had a lower occurrence of malocclusion compared to those who were weaned early.